Analisis Efisiensi dan Efektivitas Sistem Produksi dengan Metode Troubleshooting pada PT Chandra Nugerah Cemerlang - Hia, Sefania; Wiyatno, Tri Ngudi; Putra, Fibi Eko (VISA: Journal of Vision and Ideas, 2024)
PT Chandra Nugerah Cemerlang is a company that operates in the production of motorcycle and car components. To streamline its production, PT Chandra Nugerah Cemerlang uses production factors including raw materials, labor, capital, and specific technology. The main goal is to maintain and expand market share through good production results. Based on the above background, researchers are interested in knowing the extent of efficiency and effectiveness capacity of the production factors at PT Chandra Nugerah Cemerlang, especially labor and machine factors. CNC Group operates in manufacturing and engineering, producing components and spare parts for two-wheeled and four-wheeled vehicles using pressing and welding processes. PT Chandra Nugrah Cemerlang has customers such as Yamaha, Suzuki, and Kawasaki. One of the production processes to be analyzed is the welding robot line at PT CNC 2, which includes 18 robot welders and 3 Otc Daihen manual welding machines. Manual welding is used to fix suboptimal results from the robot welding. PT CNC Group is also committed to improving culture, human resources, and productivity to face global competition.